Analisis Penerapan Integrated Tug Barge Sebagai Angkutan Batu Bara Di PT. Bara Jaya Bersama - Catur Daminto; Purwanto (Pusat Riset dan Inovasi Nasional, 2023)
Coal mining activities cannot be separated from the distribution of mining products. The distribution of coal in Kalimantan is currently still dominated by sea routes. Transportation of coal by sea using ships can maximize transportation because the amount transported is more and is considered to be cheaper and more effective. Integrated Tug Barge (ITB) is a barge propelled by specially configured tugboats. When the tug and barge are connected, they form a unit that functions as a ship. Integrated Tug Barge (ITB) can be an alternative choice compared to conventional ships of the same size. There are various variables that can affect the effectiveness of using ITB as an alternative to coal loading. In this study, three research variables will be analyzed, namely costs, transportation capacity and speed/cycle as independent variables and the potential for implementing ITB as the dependent variable. The purpose of this study was to analyze whether the positive influence individually between the independent variables cost, transport capacity and speed/cycle on the dependent variable, namely the potential for implementing ITB. In this study, the object taken was the employee of PT Bra Jaya Bersama.